2009
DOI: 10.1007/s11547-009-0401-y
|View full text |Cite
|
Sign up to set email alerts
|

Role of diffusion- and perfusion-weighted MR imaging for brain tumour characterisation

Abstract: DWI has an important role in the differential diagnosis of cystic cerebral masses but not in tumour characterisation. PWI is helpful in differentiating high-from low-grade gliomas and lymphomas from high-grade gliomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 23 publications
1
39
0
2
Order By: Relevance
“…4). Differentiation between benign and malignant tumours, as well as tumour grading, can be improved using information related to regional blood flow parameters, as areas of increased microcirculation have been shown to correspond well with areas of active tumour growth [32,37]. For diagnosis and follow-up of brain neoplasms, the rCBV and the form of the SI time curves are of greatest interest [34,36,38,39].…”
Section: Applications Of Contrast-enhanced Mri In Neuroimagingmentioning
confidence: 99%
“…4). Differentiation between benign and malignant tumours, as well as tumour grading, can be improved using information related to regional blood flow parameters, as areas of increased microcirculation have been shown to correspond well with areas of active tumour growth [32,37]. For diagnosis and follow-up of brain neoplasms, the rCBV and the form of the SI time curves are of greatest interest [34,36,38,39].…”
Section: Applications Of Contrast-enhanced Mri In Neuroimagingmentioning
confidence: 99%
“…2.29). Selective analysis of solid tumor areas may help improve accuracy of ADC in predicting tumor cellularity and grade, but even when only the solid portion or darkest area on ADC is used for analysis, there is marked variation in the ADC values [269][270][271][272]. For example, when the reported ADC values from three studies that found a difference between high-grade and low-grade malignant tumors are combined, the mean ADC values for high-grade tumors are between 520 to 1,130 × 10 −6 mm 2 /s compared to 1,010 to 1,350 × 10 −6 mm 2 /s for low-grade tumors, with much greater variation between the ADC of individual cases [269][270][271].…”
Section: Primary Glial Neoplasms and Intracranial Metastasesmentioning
confidence: 99%
“…Increased cellularity and higher grade of malignant intracranial metastases tend to correlate inversely with the tumor ADC values, but similar to primary brain tumors there is substantial variability and overlap between low-grade and highgrade tumors and between metastases and primary brain tumors [272,274]. Some studies have found that analysis of ADC of peritumoral "edema" can be helpful for distinguishing different tumor types.…”
Section: Primary Glial Neoplasms and Intracranial Metastasesmentioning
confidence: 99%
“…Diffusion weighted imaging (DWI) represents a new perspective of MR applied to the study of abdominal pathologies, is based on the diffusion motion of water molecules [2] and displays information about extracellular compartment, tissue cellularity and the integrity of the cellular membranes [3]. This technique has been applied in oncological setting, in the detection and characterization of cerebral, thoracic, abdominal neoplastic lesions and in the evaluation of tumoral response to chemioterapic treatments [4][5][6][7]. Other applications are represented by the study of inflammatory diseases of the brain, kidney, liver [8][9][10].…”
Section: Introductionmentioning
confidence: 99%